2021
DOI: 10.1089/tmj.2021.0228
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Telehealth Services in Children with Cystic Fibrosis During Coronavirus Disease 2019 Outbreak

Abstract: Objectives: This study aimed to monitor the health and nutritional status of pediatric cystic fibrosis (CF) patients via telehealth services during the novel coronavirus disease 2019 . Additional aims were to determine the level of anxiety in the patients and their caregivers and to determine the COVID-19 transmission status among CF patients. Materials and Methods: The CF team supported the patients via remote contact. During telehealth services interviews, in addition to obtaining information about the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A Turkish study by Senkalfa et al revealed that CF children had lower levels of anxiety than their healthy peers; however, their mothers and the mothers of healthy children reported higher levels of anxiety during the pandemic [ 42 ]. Beşer et al found statistically significant lower anxiety prevalence in children with CF than amongst healthy children [ 43 ]. These results are similar to ours, and we found that age was positively correlated with GHQ-12 scores, indicating that the mental health of people with CF deteriorates with age.…”
Section: Discussionmentioning
confidence: 99%
“…A Turkish study by Senkalfa et al revealed that CF children had lower levels of anxiety than their healthy peers; however, their mothers and the mothers of healthy children reported higher levels of anxiety during the pandemic [ 42 ]. Beşer et al found statistically significant lower anxiety prevalence in children with CF than amongst healthy children [ 43 ]. These results are similar to ours, and we found that age was positively correlated with GHQ-12 scores, indicating that the mental health of people with CF deteriorates with age.…”
Section: Discussionmentioning
confidence: 99%
“…During COVID-19, the introduction of telehealth services for the management of children with CF was associated with reduced patient and parental anxiety and increased level of confidence in managing complications. 27 However, some pediatric centers have found that remote consultations can sometimes be less effective, especially with regard to the engagement of teenagers and safeguarding issues. In addition, children can on occasion be absent from the consultations, which is undesirable.…”
Section: Remote Care and Telehealthmentioning
confidence: 99%